2018
DOI: 10.1080/00365521.2018.1543451
|View full text |Cite
|
Sign up to set email alerts
|

Targets for interventions for faecal incontinence in inflammatory bowel disease: a systematic review

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…We therefore used the word 'urgency' as a euphemism for 'incontinence', to respect patient preference. The topic guide [Table 1] was developed in partnership with our PPI panel and informed by our previous studies 6, [13][14][15][16] , systematic reviews 17,18 and knowledge of issues with development of online self-management programmes [19][20][21] . During focus groups, one team member facilitated the discussion whilst another acted as observer, taking field notes including a sketch of the layout, seating arrangement and first names of participants, and brief notes on the dialogue.…”
Section: Data Collectionmentioning
confidence: 99%
“…We therefore used the word 'urgency' as a euphemism for 'incontinence', to respect patient preference. The topic guide [Table 1] was developed in partnership with our PPI panel and informed by our previous studies 6, [13][14][15][16] , systematic reviews 17,18 and knowledge of issues with development of online self-management programmes [19][20][21] . During focus groups, one team member facilitated the discussion whilst another acted as observer, taking field notes including a sketch of the layout, seating arrangement and first names of participants, and brief notes on the dialogue.…”
Section: Data Collectionmentioning
confidence: 99%
“…Although physiological triggers may differ, similar affective, cognitive, and behavioral responses to symptoms appear to exacerbate and maintain symptoms across long-term conditions [ 49 ]. A number of systematic reviews have identified specific cognitive, behavioral, and emotional factors associated with fatigue, pain, and urgency, along with other psychological factors [ 7 , 15 , 16 , 50 , 51 ]. Anxiety and depression were found to be associated with each symptom independent of disease activity.…”
Section: Resultsmentioning
confidence: 99%
“…In IBD, pain, acceptance, pain self-efficacy, and mental well-being are associated with lower pain severity and pain-related disability [ 53 , 56 ]. A range of safety-seeking and avoidance behaviors designed to avert the possibility of incontinence was identified as often having a significant cognitive and affective burden [ 8 , 16 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major symptoms of UC are diarrhea, bloody stools, abdominal pain [1][2][3], urgent and nocturnal defecation. Urgent defecation has been identi ed as an important symptom in many studies [4][5][6][7], is emphasized in the United States guidelines, and is used as a success index for diagnosis and treatment [8]. An online survey of Japanese UC patients con rmed that urgent defecation correlates with a decrease in the patient's quality of life (QOL) [4].…”
Section: Introductionmentioning
confidence: 99%